LEBANESE ARMENIANS; A DISTINCTIVE COMMUNITY IN THE ARMENIAN DIASPORA AND IN LEBANESE SOCIETY - Abramson, Scott (The Levantine Review, 2013)
Lebanon, for many Armenians, is referred to as “our second homeland” (yergort hayrenik), and it is scarcely difficult to see why. As nowhere else in the regional diaspora, Lebanon has offered its Armenian citizens—initially refugees—the economic freedom to achieve prosperity, the political freedom to pursue their interests, and the communal autonomy to preserve their identity. These freedoms and the efflorescence that they have enabled—to say nothing of Lebanon’s singularity as the scene of unique Armenian ecclesiastical and cultural institutions—have made Lebanon a distinctive part of the Armenian diaspora. This study aims to demonstrate why this was—and continues to be—the case.